2016
DOI: 10.1590/s0102-865020160040000006
|View full text |Cite
|
Sign up to set email alerts
|

Medical ozone treatment ameliorates the acute distal colitis in rat

Abstract: PURPOSE:To investigate the effect of medical ozone treatment on the experimental acute distal colitis in rats. METHODS:Eighteen rats were randomly distributed into three equal groups; control, acute distal colitis (ADC) without and with medical ozone treatment. Rats in the control group were taken saline. ADC was performed by rectal way with 4% acetic acid in groups 2 and 3, and the group 3 was treated with medical ozone for three weeks both rectally and intraperitoneally. At the twenty second day the distal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…[7][8][9][10][11][12][13] Recently, conclusive evidence has been provided that low O 3 concentration increases the nuclear translocation of Nrf2, thus inducing the Nrf2-mediated Keap1-dependent transcription of ARE-driven genes. 14 Thus, robust clinical indication and growing scientific data support the efficacy of O 3 therapy in various medical fields such as e.g., orthopedics, [15][16][17] gastroenterology, [18][19][20] pneumology, 21,22 dentistry. [23][24][25] However, doubts persist about potential negative side effects of O 3 administration.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Recently, conclusive evidence has been provided that low O 3 concentration increases the nuclear translocation of Nrf2, thus inducing the Nrf2-mediated Keap1-dependent transcription of ARE-driven genes. 14 Thus, robust clinical indication and growing scientific data support the efficacy of O 3 therapy in various medical fields such as e.g., orthopedics, [15][16][17] gastroenterology, [18][19][20] pneumology, 21,22 dentistry. [23][24][25] However, doubts persist about potential negative side effects of O 3 administration.…”
Section: Introductionmentioning
confidence: 99%
“…In an animal study of Aslaner et al, medical ozone treatment was studied in the acute distal colitis; they have found its possible effect is by means of decreasing inflammation, edema, and affecting the proliferation and the vascularization to treat acute distal colitis (22). We think that the underlying mechanism of medical ozone treatment's anti-inflammatory effect can be a decrease in oxidative stress.…”
Section: Discussionmentioning
confidence: 98%
“…In parallel to clinical advancement, an increasing number of scientific reports have been published on the biomedical effects of O 3 as adjuvant/alternative therapeutic approach for e.g., pain management [18,19,20,21,22], gastrointestinal diseases [23,24,25,26,27], lung diseases [28,29,30,31], diabetes [32,33,34,35,36,37], ischemia [38,39,40,41,42,43], cancer [44,45,46], infective diseases [47,48,49,50], dentistry [51,52,53,54,55,56].…”
Section: Ozone In the Biomedical Fieldmentioning
confidence: 99%